Distributed and parallel systems : (Springer, 2007)
Distributed and Parallel Systems: From Cluster to Grid Computing is an edited volume based on DAPSYS 2006, the 6th Austrian-Hungarian Workshop on Distributed and Parallel Systems, which is dedicated to all aspects of distributed and parallel computing. The workshop was held in conjunction with the 2nd Austrian Grid Symposium in Innsbruck, Austria in September 2006. Distributed and Parallel Systems: From Cluster to Grid Computing is designed for a professional audience composed of practitioners and researchers in industry. This book is also suitable for advanced-level students in computer science.